Prototype of Fuel Liquid Level Monitoring System at Gas Station Hidden Tank Using the Internet of Things (IoT) - Novianti, Triuli; Winarno, Winarno (Jurnal Teknik Elektro dan Komputer TRIAC, 2024)
Currently, the availability of fuel oil (BBM) to the community is critical. One way to anticipate delays in supply and empty fuel stocks at refueling stations (petrol stations) is to periodically monitor the fuel liquid level with a Stick Sounding Meter measuring device dipped in the bottom of the tank. Monitoring uses the Internet of Things (IoT) concept, which can integrate surveillance system devices with the Internet network. The system uses an ultrasonic sensor mounted horizontally on the tank's liquid surface to detect the fluid level's distance and an ESP32 NodeMCU to communicate with ThingSpeak, an IoT device. If the tank's liquid exceeds 20% of its capacity, the test results will be displayed in real-time onThingSpeak, and a notification will be sent to the field. Therefore, both petrol station officers in the field and admins can monitor more efficiently. Ultrasonic sensor tests, data transmission accuracy, and fuel liquid levels are some of the stages carried out. Tank 1 has an accuracy rate of 97.066%, and Tank 2 has an accuracy rate of 95.451%.Bahasa IndonesiaSaat ini, ketersediaan bahan bakar minyak (BBM) bagi masyarakat sangat penting. Salah satu cara untuk mengantisipasi keterlambatan pasokan dan kekosongan stok BBM pada SPBU [LXC1] adalah dengan memantau level cairan BBM secara berkala dengan alat ukur Stick Sounding Meter [LXC2] yang dicelupkan di dasar tangki. Monitoring menggunakan konsep Internet of Things [LXC3] (IoT) yang dapat mengintegrasikan perangkat sistem pengawasan dengan jaringan internet. Sistem ini menggunakan sensor ultrasonic [LXC4] yang dipasang secara horizontal pada permukaan cairan tangki untuk mendeteksi jarak level cairan dan NodeMCU ESP32 untuk berkomunikasi dengan ThingSpeak, perangkat IoT. Apabila jumlah cairan dalam tangki kurang dari 20% dari kapasitasnya, hasil pengujian akan ditampilkan secara realtime pada ThingSpeak dan notifikasi akan dikirim ke lapangan. Oleh karena itu, baik petugas SPBU di lapangan maupun admin dapat memonitor dengan lebih efisien. Uji sensor ultrasonik, tingkat ketepatan pengiriman data, dan tingkat cairan BBM adalah beberapa tahapan yang dilakukan. Tangki 1 memiliki tingkat akurasi 97,066%, dan tangki 2 memiliki tingkat akurasi 95,451%.